2006
DOI: 10.1037/0033-3204.43.3.271
|View full text |Cite
|
Sign up to set email alerts
|

The working alliance: Where are we and where should we go?

Abstract: This article describes important findings that have emerged from decades of research on the working alliance, as well as some of the clinical implications of these findings. In addition, future directions of research on this construct are suggested. Our hope is that this article will provide useful heuristics for better understanding the alliance, the therapeutic relationship more broadly, and the process of therapeutic change in general. (PsycINFO Database Record (c) 2010 APA, all rights reserved).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
283
1
10

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(301 citation statements)
references
References 56 publications
7
283
1
10
Order By: Relevance
“…The results of two meta-analyses show a significant effect between working alliance and positive therapy outcome (Horvath & Symonds, 1991;Martin, Gaske, & Davis, 2000). In addition, as suggested by Castonguay, Constantino, and Holtforth (2006), the concept of the working alliance holds such an important place in what is thought of as "good therapy" that it appears unimaginable not to include this variable in a study examining the process or outcome of psychotherapy. We believe it should be the same for studies examining the process and the outcomes of executive coaching.…”
Section: The Coach-coachee Relationship In Executive Coachingmentioning
confidence: 87%
See 1 more Smart Citation
“…The results of two meta-analyses show a significant effect between working alliance and positive therapy outcome (Horvath & Symonds, 1991;Martin, Gaske, & Davis, 2000). In addition, as suggested by Castonguay, Constantino, and Holtforth (2006), the concept of the working alliance holds such an important place in what is thought of as "good therapy" that it appears unimaginable not to include this variable in a study examining the process or outcome of psychotherapy. We believe it should be the same for studies examining the process and the outcomes of executive coaching.…”
Section: The Coach-coachee Relationship In Executive Coachingmentioning
confidence: 87%
“…However, results thus far have not been conclusive. Castonguay et al (2006) have suggested that more studies are needed to clarify the issue of the direction and nature of the alliance' s impact on the process and outcome of treatment. To our knowledge, no empirical study has examined the role of the working alliance in the relation between coaching and the outcomes of coaching.…”
mentioning
confidence: 99%
“…In particular, working alliance, also referred to as therapeutic bond, alliance, or therapeutic alliance, is a collaborative relationship between patient and provider and has been associated with positive psychotherapy outcomes for a wide range of diagnoses and populations, including patient engagement and retention in treatment, (Castonguay, Constantino, & Holtforth, 2006;Sharf, 2010). It is conceptualized as a key ingredient of therapeutic relationship and a strong mediator of behavioral change by facilitating for patients and providers emotional involvement, trust, partnership, and commitment to the goals and therapeutic process (Bordin, 1979;Castonguay et al, 2006;Horvath, 1991). …”
Section: Introductionmentioning
confidence: 99%
“…After decades of substantial empirical attention, the alliance has been consistently and robustly associated with patient engagement and improvement across a variety of clinical problems, forms of treatment, and theoretical perspectives (see Castonguay, Constantino, & Holtforth, 2006). Three systematic meta-analyses of this association have demonstrated overall Cohen's (1988) d effect sizes between .21 and .26 (Horvath & Bedi, 2002;Horvath & Symonds, 1991;Martin, Garske, & Davis, 2000), showing a stronger relation with outcome than specific techniques (see Wampold, 2001).…”
Section: Introductionmentioning
confidence: 99%